P380 The association between social support, violence experience, and social service needs among a select sample of urban adults. (14th July 2019) - Chandran, Aruna; Long, Amanda; Kingon, Yvonne; Murray, Jeannie; Fields, Errol; Schumacher, Christina; Greenbaum, Adena; Jennings, Jacky
Abstract : Background: Experiencing violence is associated with negative health outcomes including increased substance use, mental health problems, and sexual risk behaviors. Studies show associations between strong perceived social support and decreased negative health outcomes. The objectives of this study were: (1) determine the impact of violence (exposure and victimization) on social service needs and perceived health status, and (2) assess whether social support is associated with decreased violence experience among a select sample of urban adults. Methods: A cross-sectional survey was conducted among 187 adults seen in one of 7 urban clinics as part of a larger project between September 2015 and March 2018. A multivariable logistic regression model was used, adjusting for the clinic site as well as age and gender identity. Results: 131 (72%) individuals had ever witnessed and 89 (49%) had ever experienced physical assault. Violence victimization was associated with an 8.6-fold odds (95% CI: 2.4, 31.4) of needing housing assistance and 3.4-fold increased odds (95% CI: 1.4, 8.5) of needing mental health/substance use support services. Exposure to violence was associated with a 5.2-fold increased odds (95% CI: 2.0, 13.4) of needing housing assistance, a 12.4-fold increased odds (95% CI: 2.1, 74.0) of needing transportation support, and a 0.5 decreased odds (95% CI: 0.3, 0.8) of reporting optimal health status. Increased perceived social support was associated with 0.54 odds (95% CI: 0.4, 0.8) and 0.62 odds (95%CI: 0.4, 0.9) of violence exposure and victimization, respectively. Conclusion: Violence experiences were common in this sample of urban adults, and were associated with increased social service needs and suboptimal perceived health status. Augmenting sources of social support is one possible mechanism for addressing these issues. Including care for the effects of experiencing violence as well as social service needs are important in optimizing the health of key populations. Disclosure: No significant relationships.